Accessibility of the histone H3 tail in the nucleosome for binding of paired readers - Jovylyn Gatchalian (Nature Portfolio, 2017)
The chromatin remodeller CHD4 contains two PHD finger reader domains that have been shown to bivalently recognize H3 histone tails. Here, the authors describe a mechanism by which the PHD fingers bind to the intact nucleosome core particle, revealing both cooperative and individual interactions.